Effects of age, viewing distance and target complexity on static ocular counterroll - Goltz, Herbert C.; Mirabella, Giuseppe; Leung, Joanne C.Y.; Blakeman, Alan W.; Colpa, Linda; Abuhaleeqa, Khaled; Wong, Agnes M.F. (Vision research (Oxford), 2009)
The ocular counterroll (OCR) reflex generates partially compensatory torsional eye movements during static head roll tilt. We assessed the influence of age, viewing distance and target complexity on the OCR across the age span (13–63 years; n = 47), by recording eye movements during head-on-body roll tilt (0 ± 40° in 5° steps) while subjects viewed simple vs. complex targets at 0.33 and 1 m. We found that subjects ⩾31 years had lower gains than those ⩽30 years, but only for far targets. Consistent with prior reports, far targets elicited higher OCR gains than near targets, and target complexity had no effect on gains, suggesting that visual input is primarily used to maintain vergence during OCR.